-7(-3-x)=-2(2-x)

Simple and best practice solution for -7(-3-x)=-2(2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-3-x)=-2(2-x) equation:



-7(-3-x)=-2(2-x)
We move all terms to the left:
-7(-3-x)-(-2(2-x))=0
We add all the numbers together, and all the variables
-7(-1x-3)-(-2(-1x+2))=0
We multiply parentheses
7x-(-2(-1x+2))+21=0
We calculate terms in parentheses: -(-2(-1x+2)), so:
-2(-1x+2)
We multiply parentheses
2x-4
Back to the equation:
-(2x-4)
We get rid of parentheses
7x-2x+4+21=0
We add all the numbers together, and all the variables
5x+25=0
We move all terms containing x to the left, all other terms to the right
5x=-25
x=-25/5
x=-5

See similar equations:

| -6(b+3)+6b=6b=-6(-4b+3) | | k/8=0.8k= | | 6(4+5a)+10a=-10(1-6a)-6 | | 3(–4z+6)=–(12−6z) | | 18-3t=-12 | | -20k-13k+-11=10 | | 8(x+9)=72-5x | | 2k+18=0 | | 12(n)=5n-6 | | -10b-3+3b=4-6b | | 18=14.5m=6m+12 | | 6n3=15 | | 121/2=2w+2(31/2) | | -6+n=-3 | | p-9=-5(p-3) | | .15-3x=-6 | | 7(x+2)-1=3x+4(3+x) | | -8x-7=-3x-17 | | 6x+5-9x=-40 | | 7x=7(7)=0 | | (2x²-3x+1)=+(4x-7) | | 0.66666667n-5=-2 | | 14=2(r-9) | | –10b−3+3b=4−6b | | 10m-19=3m+2 | | 4u+5=37 | | -7(4x+7)=3+4(-4-6) | | 15(x+14)=60 | | T(12)=5n-6 | | -8x3=-6x11 | | -11=k+(+5) | | 9x+54=99 |

Equations solver categories